Pelatihan Pendampingan Sertifikasi Halal Untuk Meningkatkan Nilai Jual Produk UMKM - Faisal, A.; Kholifatul M, Dewi; Oktafia R, Erita; Prima, Anggra; Firdaus, Firdaus (MAYARA: Jurnal Pengabdian Masyarakat, 2024)
Organizing halal certification assistance training is an effective strategy for increasing the capacity of MSMEs to understand, implement, and maintain halal standards. Through this training, MSMEs are given practical and sustainable guidance to fulfil halal certification requirements so that they can compete in the domestic and national markets. As trade, or buying and selling, develops, the need for halal products also increases and is in great demand. Halal is good or holy and not dangerous. This condition was utilized by students of the Sangatta Islamic College (STAI) Field Work Lecture (KKL) to provide space for MSMEs in Lake Redan Village to carry out halal certification. MSME products that take part in halal certification training are directed and guided to be able to enter the official website following the provisions. This training aims to provide a comprehensive understanding of the requirements, processes, and practical implementation of halal certification to MSMEs. By increasing understanding and compliance with halal standards, it is hoped that MSMEs can increase the selling value of their products, access a wider market, and strengthen the sustainability of their business.